Clinical Evaluation of Lesion Sterilisation and Tissue Repair Therapy using Bioceramic in Deciduous Molars with Chronic Periapical Periodontitis and Pulp Necrosis: A Randomised Controlled Trial - Jin Sun; Jiahui He; Wei Luo; Min Wu; Yun Liu (Journal of Clinical and Diagnostic Research)
Introduction: Lesion Sterilisation and Tissue Repair Therapy (LSTR) has proven to be as effective as Root Canal Therapy (RCT) for treating deciduous molars with chronic periapical periodontitis and pulp necrosis. Given the routine use of a three-antibiotic mixture, it is important to investigate a more effective medication that offers antibacterial properties, good biocompatibility, and stable chemical characteristics. Aim: To evaluate the efficacy of LSTR with bioceramic (LSTR-bioceramic) in deciduous molars with chronic periapical periodontitis and pulp necrosis. Materials and Methods: A randomised controlled trial was conducted in the Stomatological Healthcare Centre, Shenzhen Maternity and Child Healthcare Hospital affiliated to Southern Medical University, Shenzhen, Guangdong, China, from January 2022 to December 2023. The study included 88 children aged 3-8 years, all diagnosed with chronic periapical periodontitis and pulp necrosis. These cases were treated according to the study protocol, with 44 subjects receiving RCT and the other half receiving LSTR therapy. The subjects were followed-up clinically and radiologically at six and 12 months. The results were rigorously analysed using a Z-test, with a significance level established at 0.05. Results: At six months, the clinical success rates of LSTR-bioceramic and RCT were 37 (84.09%) and 41 (93.18%), respectively; the radiological success of them were 39 (88.64%) and 37 (84.09%). And at 12 months, the clinical success rates of LSTR-bioceramic and RCT were 31 (73.81%) and 35 (81.4%), respectively; the radiological success of them were 25 (59.52%) and 27 (62.79%). No statistically significant differences were found between the radiological and clinical successes of two groups at six months and 12 months (p=0.093, 0.221, 0.456, and 0.271, respectively). Conclusion: LSTR-bioceramic can be used as an effective treatment for deciduous molars with chronic periapical periodontitis and pulp necrosis.